Peningkatan Hasil Belajar Siswa Menggunakan Model Pembelajaran Role Playing pada Tematik Terpadu Sekolah Dasar - Kaffa, Zelmi; Yunisrul, Yunisrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
Improving Student Learning Results Using Role Playing Learning Models In Basic School Integrated Thematics Abstract          The research used was Classroom Action Research (CAR). The purpose of this study was to describe the increase in student learning outcomes in integrated thematic learning using the Role Playing learning model in class IV SD Negeri 10 Sapiran, Bukittinggi City. The research subjects were teachers (practitioners) and 29 students. The research location is SD Negeri 10 Sapiran, Bukittinggi City. The results showed an increase in: a) RPP observation of the first cycle was 84.72 (B)%, the second cycle was 94.44% (A); b) Observation aspect of the first cycle teacher is 78.40% (C), the second cycle is 95.45% (A); c) Observation aspects of the student's first cycle is 81.81% (C) and the second cycle is 93.18% (A); d) learning outcomes in the first cycle are 66.58 (D) and the second cycle is 86.35 (B).  Keywords: Integrated thematic learning, Role Playing models.